Hak Kebebasan Berpendapat dalam Hubungannya dengan Pencemaran Nama Baik Menurut KUHP; Perspektif Teori Maqâs?id Sharî’ah - Moh. Faizur Rohman (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2017)
Human rights are often echoed by various parties are sometimes opposed to each other. Many journalists who exercised the right to freedom of expression expressed the opinion that the right has been protected by the 1945 Constitution article 28 E (3), precisely resulting in a criminal offense of defamation for those who do not like it. Defamation articles in the Criminal Code are often regarded as a powerful weapon against a criticism as a form of antipathy against criticism. Therefore, there should be efforts to classify the forms of the use of rights and forms of criminal acts. and will be seen from the standpoint of maqâs?id sharî’ah. Through approach statue approach, and case approach, obtained that the law has protected the rights of everyone in expressing opinions. Every person shall have the right and freedom to express opinions but such rights shall not infringe the rights of others. In maqâs?id is guaranteed and protected self-esteem, the soul for every human being is contained in the principle of h?ifd?u al-nafs wa al-‘ird. Therefore, in every opinion, communicate and socialize should pay attention to the rights of others is the dignity of one's dignity to create a balanced and harmonious life.